1983
DOI: 10.1038/bjc.1983.55
|View full text |Cite
|
Sign up to set email alerts
|

Decreased blood histamine levels in patients with solid malignant tumours

Abstract: Summary In a one-year follow-up study, 444 blood histamine determinations were performed in 163 patients with solid malignant tumours. Compared with normal subjects, blood histamine levels were significantly lower in patients with unresected primary tumours (30.7 + 19.9 ngml -), metastases (34.1 + 17.1 ngml -), or both (24.5+12.8ngml-1). By contrast, after successful tumour resection, histamine blood levels were nearly normal (52.1 + 18.4 ng ml -, versus 59.6 + 22.6 in control patients). Stability of the hista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In support of the notion that histamine can induce effects long after its catabolism, Burtin and colleagues have demonstrated effects of subcutaneous injections of histamine on the growth of a fibrosarcoma and a lung carcinoma in mice. These authors show that histamine treatment delayed tumour development, but the anti-tumour effector mechanism was not disclosed [20,21,28].…”
Section: Discussionmentioning
confidence: 97%
“…In support of the notion that histamine can induce effects long after its catabolism, Burtin and colleagues have demonstrated effects of subcutaneous injections of histamine on the growth of a fibrosarcoma and a lung carcinoma in mice. These authors show that histamine treatment delayed tumour development, but the anti-tumour effector mechanism was not disclosed [20,21,28].…”
Section: Discussionmentioning
confidence: 97%
“…Up to now, we found normal BHL in noncancer patients suffering from chronic severe disease [1], To our knowledge, BHL have not been studied in infants and children infected with hu man immunodeficiency virus type 1 (HIV-1). This study was further prompted by the demonstration of surface CD4 molecules on cultured basophils [2] and the report of atopic manifestations in patients with acquired immunodeficiency syndrome (AIDS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In order to take into consideration possible diurnal variations in blood histamine [6], blood was always taken between 9.00 and 11.00 h and treated as previously described [1]. Briefly, to 200 pi of heparinized venous blood were added 800 pi NaCl 0.15 Mand 1 ml perchloric acid 0.8 N. After vigourous agitation and centrifugation, supernatants were stored in polystyrene tubes until assay.…”
Section: Histamine Determinationmentioning
confidence: 99%
“…The mechanisms involved in tumor control through aller gic sensitization have still to be clarified, but at the present time it could be speculated that the release of chemical mediators with vasoactive properties, such as histamine and serotonin, into the circulation, could account for an increase of vascular permeability which would in turn enhance the access of humoral and cellular cytotoxic effectors into the tumor tissues. Interestingly, Burtinet al [25,26] have shown that his tamine or serotonin injection into tumor-bearing mice can prevent tumor growth, and more recently the same authors have found low histamine blood le vels in patients with progressive primary or metastatic cancer [27],…”
Section: Discussionmentioning
confidence: 99%